TEACHING READING SKILL BY USING SAVE THE LAST WORD FOR ME AND DOUBLE-ENTRY JOURNAL STRATEGIES AT JUNIOR HIGH SCHOOL - Ulfa Yuliasari (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2018)
In this study was discussed to how teaching reading is one of the important skills in English that should be taught by teachers to students. In this case a teacher should be creative and innovative to make learning reading more enjoyable and the students are interested and motivated to learn it. One of them is by applying interesting strategies that are suitable for teaching reading. So, in this study the author discusses about two strategies, there are save the last word for me and double-entry journal strategies. Both of them are strategies that helps students more understand about the text read by using a small paper (note taking) which consists of two columns to make students more critical in comment it on important points in the text. This strategy is not only able to make students interested and motivated for reading lessons, but students are also able to better understand the contents of a text story, while students are able to understand the general structure (generic structure) of the text. Thus, in learning reading is not boring for students.